Location information and pictures of the OASIS Barrow field intensive Spring 2009, Version 1.0 ... - NCAR Atmospheric Chemistry Division ACD (UCAR/NCAR - Earth Observing Laboratory, 2012)
The Ocean Atmosphere Sea Ice Snowpack (OASIS) field campaign was designed to provide a detailed study of atmosphere-cryosphere exchange processes occurring in the Arctic in late winter / early spring and the impact these exchange processes have on the oxidizing capacity of the remote Arctic atmosphere, with an eye toward the understanding of how these processes will evolve in a changing climate. This dataset contains location information in KML and TIFF formats. ...